Análisis del rol de la estación radial diblu en el comportamiento de las barras bravas de Guayaquil - Banda Andrade, Xiomara Madelayne (2017)
In this thesis, the scientific process of obtaining results allows to identify the causes, achieving with the development of research that contributes to make a good information this sport case for the future of young journalists that is going to devote to this field of communication, was also Necessary to involve in the study the instruments that allowed to discover the problem of decontextualized information provided by Radio Diblu in its information page that causes discomfort of its followers, to know what the true role of journalist in this sports field. In order to carry out this thesis, it was necessary to obtain evidence to show that tabloid, yellow, and out-of-context publications cause verbal, physical violence among fans and journalists. In our country every day grows the passion for football and with them violence, the duty of a communicator is therefore to inform more not causing verbal confrontations for their information out of context to gain fame, money…………